Efficacy of corticosteroid and intravenous cyclophosphamide in acute exacerbation of idiopathic pulmonary fibrosis: A propensity score‐matched analysis. Issue 8 (25th February 2019) - Hozumi, Hironao; Hasegawa, Hirotsugu; Miyashita, Koichi; Yasui, Hideki; Suzuki, Yuzo; Kono, Masato; Karayama, Masato; Furuhashi, Kazuki; Hashimoto, Dai; Enomoto, Noriyuki; Fujisawa, Tomoyuki; Inui, Naoki; et al.
ABSTRACT: Background and objective: Acute exacerbation (AE) is a leading cause of death in patients with idiopathic pulmonary fibrosis (IPF). Although optimal treatment for AE‐IPF remains unclear, high‐dose corticosteroids (CS) with/without immunosuppressants, including intravenous cyclophosphamide (IVCY), are often used as empirical therapy. However, the survival benefit of adding IVCY to CS therapy is unknown. We investigated the efficacy of this therapy in patients with AE‐IPF. Methods: Overall, 102 consecutive patients with IPF with a first idiopathic AE were included. Post‐AE survival rates and treatment safety were retrospectively assessed. Efficacy of CS + IVCY therapy for the first AE was compared with that of CS monotherapy using a propensity score‐matched analysis. Results: The post‐AE 90‐day survival rate of the entire cohort was 64.7%. On the basis of the propensity scores, 26 matched patient pairs were made. Characteristics of matched patients with AE‐IPF treated with CS (matched CS group) and those with CS + IVCY (matched CS + IVCY group) were well balanced. No significant between‐group differences were observed in post‐AE 90‐day survival rates (84.6% vs 76.9%; P  = 0.70), cumulative survival rates ( P  = 0.57 by log‐rank test) or incidence of adverse events ≥ CTCAE (Common Terminology Criteria for Adverse Events) v5.0 grade 3 (61.5% vs 65.4%; P  = 1.00). Conclusion: The propensity score‐matched analysis demonstrated that compared with CS monotherapy, CS + IVCY therapy did not significantly improve post‐AE survival in patients with AE‐IPF. Further studies are warranted to assess the efficacy of CS + IVCY therapy for AE‐IPF. Abstract : A propensity score‐matched analysis demonstrated that in patients with idiopathic pulmonary fibrosis with a first episode of idiopathic acute exacerbation, compared with corticosteroids (CS) monotherapy, CS plus intravenous cyclophosphamide (IVCY) therapy did not significantly improve their survival. This suggests that routine use of IVCY with CS is not recommended. See related Editorial